Evolución reciente del mercado mundial de vinos y el desempe\~no de Argentina - Julio Elías; Gustavo Ferro; Álvaro García (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2019)
– How did the wine world market perform in the last decades in terms of production, international trade, prices and consumption? What happened with Argentina's wine industry in the same period? To answer these questions, we categorize countries and analyze FAO statistics from 1961 on. We verify that production, exports and consumption had displaced from traditional Old World traditional producers to New World. Production has decreased in volume, consumption has tended to reduce its dispersion regionally, the internationalization of the market had tripled in a little more than half a century and quality -proxy by export relative prices- has increased on average and has reduced its dispersion with respect to world average and to the prices of the more reputed producer and exporter.
Keywords: Q11; Q17; 330; Weinmarkt; Weinbau; Weinhandel; Argentinien; Welt